TRANSFORMING CONSUMER AND IT'S IMPLICATIONS FOR THE UKRAINIAN SOCIETY - H. Sanko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This article reviews the changes of consumption patterns in the Ukrainian society over the last 25 years and the impact this transformation had on Ukrainian consumers. The author researches the market forces and the influence those market forces had on the consumer behavior. Finally, the author concludes that the market forces present on the Ukrainian market resulted in transforming consumption patterns and consumer behavior. In this scientific research also presents a critical analysis of the implications for the Ukrainian society and the possible choices of market models.